2022
DOI: 10.3390/jcs6020046
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behaviour Evaluation of Porous Scaffold for Tissue-Engineering Applications Using Finite Element Analysis

Abstract: In recent years, finite element analysis (FEA) models of different porous scaffold shapes consisting of various materials have been developed to predict the mechanical behaviour of the scaffolds and to address the initial goals of 3D printing. Although mechanical properties of polymeric porous scaffolds are determined through FEA, studies on the polymer nanocomposite porous scaffolds are limited. In this paper, FEA with the integration of material designer and representative volume elements (RVE) was carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 58 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…The authors concluded that both cross-linking time and volume of the cross-linker were important in the modulation of the mechanical properties of the scaffolds. Also using alginate, Kakarla et al (2022) investigated the maximum stress regions and observed that the stress regions were at the soft zones near the pore area. Compared to experimental results, the stress-strain curves were similar, with a maximum strength obtained at 2.8 MPa for the experimental results and 2.7 MPa for the FE analysis.…”
Section: Finite Element Analysismentioning
confidence: 99%
“…The authors concluded that both cross-linking time and volume of the cross-linker were important in the modulation of the mechanical properties of the scaffolds. Also using alginate, Kakarla et al (2022) investigated the maximum stress regions and observed that the stress regions were at the soft zones near the pore area. Compared to experimental results, the stress-strain curves were similar, with a maximum strength obtained at 2.8 MPa for the experimental results and 2.7 MPa for the FE analysis.…”
Section: Finite Element Analysismentioning
confidence: 99%
“…These microstructures act as well-designed reinforcements that mirror the natural tissue’s ability to effectively distribute forces and endure stresses. The strategic arrangement of interwoven struts and lattice formations ensures that bioprinted constructs replicate the biomechanical integrity of native tissues, establishing a foundation for enhanced durability, resilience, and overall stability . This biomechanical resemblance bridges the elegance of natural architecture with the practical demands of functional tissue engineering.…”
Section: Role Of Trabecular Microarchitecture In Scaffold Bioactivitymentioning
confidence: 99%
“…FEA is widely used to simulate the mechanical behaviour of hydrogels, including their deformation, stress distribution, and responses to external forces [50,51]. It helps us understand how hydrogels will behave in different loading conditions and assists in designing hydrogels with specific mechanical properties for applications such as tissue engineering, drug delivery, and medical devices.…”
Section: Numerical Simulationsmentioning
confidence: 99%